Pengaruh Biaya Produksi Dan Harga Jual Terhadap Pendapatan Petani Jagung (Studi Kasus Pada Kelurahan Simboro Kabupaten Mamuju) - Rayo , Chicilia Iriani; Rusli , Rusli; Mappigau , Ernawaty (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The income of corn farmers in Simboro Village, Mamuju Regency depends on the production costs incurred by corn farmers during the increasing planting season. This is caused by the cost of renting agricultural equipment which has increased in price, and good quality corn seeds are very rare and expensive and the selling price that corn farmers get. The selling price during the harvest season is uncertain or experiences a decline which often makes farmers feel threatened with losses so that the selling price of their agricultural products can affect the income level of corn farmers. This research aims to determine and explain the influence of production costs and selling prices on the income of corn farmers, Simboro Village, Mamuju Regency. The research method used is a quantitative method with the data source used being primary data, namely data obtained directly from distributing questionnaires to corn farmers in Simboro Village, Mamuju Regency. The population in this research is corn farmers in Simboro Village, Mamuju Regency. The number of corn farmers is 30 people. In this research, sampling used a non-probability saturated sampling technique, that is, the entire population was sampled. The data analysis technique used in this research is using the classic assumption test and multiple regression analysis. The research results show that production costs have a significant effect on the income of corn farmers in Simboro Village, Mamuju Regency. Selling prices have a significant effect on the income of corn farmers in Simboro Village, Mamuju Regency. Production costs and selling prices simultaneously have a significant effect on the income of corn farmers in Simboro Village, Mamuju Regency.